Analisis Deiksis pada Novel “Rembulan Tenggelam Di Wajahmu” Karya Tere Liye Serta Pemanfaatannya pada Materi Ajar Teks Novel - Arneta Destria Kirana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Deixis is a word that has a referent or reference that changes depending on who is speaking and the context of the conversation. Deixis can also be useful in direct or verbal communication activities. Examples of the benefits of deixis in indirect communication can be realized in literary works in the form of novels. In connection with the research to be conducted, the researcher chose the novel Rembulan sinks in your face as the research subject. Therefore, this research wants to examine the types, forms and functions of deixis as well as the use of deixis in the novel